ANALISIS KINERJA KEUANGAN PADA PEMERINTAH DAERAH KOTA MALANG DAN KOTA SURABAYA TAHUN ANGGARAN 2004-2012 - Rachman, Rieke Faradila (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research was aim to: (1) comparing monetary performance of local government of town of Malang and town of Surabaya in the budget year 2004 until 2012. (2) To know monetary performance picture of town area of Malang and town of Surabaya in last nine years (2004-2012) and (3) to know revenue plan performance and area expense (APBD) at government of town of Surabaya and Town of Malang in 2004-2012 evaluated from monetary independence ratio of area, ratio of effectiveness PAD and monetary efficiency of area, compatibility ratio, and growth. Keywords: performance analysis of government finance